Analisis Permasalahan Konseptual Bunga Pinjaman Pemegang Saham pada Peraturan Pemerintah No. 94 Tahun 2010 - Bintoro, Wandha Benny; Dewi, Gemala (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
The Article 12 of Government Regulation No. 94 of 2010 (“PP No. 94/2010”) has conceptual problems as it forces the imposition of interest on loans given by shareholders to the limited liability company Taxpayer. The purpose of this study is to analyze the imposition of loan interest accroding to the concept of loan in Indonesian Civil Code and the application of Islamic Law in Indonesia associated with the spiritual rights as the Moslem citizen to implement Islamic law under the Indonesian Constitution. The results of the study indicate that imposing the interest is not a mandatory requirement of loan according to the Indonesian Civil Code and this also is contrary to Article 29 of the Indonesian Constitution because it prevents the parties from implementing Islamic law by not imposing loan interest (riba). Based on the study results, the provisions in Article 12 of PP No. 94/2010 need to be amended to solve the conceptual problem of implementing shareholder loan interest.